Techniques of industrial policy formation - Shestakova, Kristina V.; Karpenko, Elena M. (Journal of the Belarusian State University. Economics, 2024)
The article presents a complex methodology of industrial policy investigation. Pieces of evidence of industrial policy signiﬁcance for a successful country’s industrial development are mentioned. The current state of industrial sector development in Belarus is analysed. The main failures and problems in the industry sector and industrial policy design in Belarus are identiﬁed. The uniqueness of this study lies in the investigation of the mechanism for industrial policy design using speciﬁc authors’ metrics for a country’s industrial development: degree of industrialisation (DI) and competitive industrial performance index (CIP). Based on these metrics, stages of industrial development of a country are identiﬁed and an algorithm for industrial policy investigation is concluded. Several methodological instruments for the country’s industrial development analysis are proposed: matrix DI – CIP for determining the current state of the country’s industrial development and matrix Sc – Dev for industrial policy tools selection. According to the position of a country in the matrix DI – CIP, a type of appropriate industrial policy is introduced and a path for further industrial development could be considered. Matrix Sc – Dev provides a scientiﬁc approach to the justiﬁcation of industrial policy diﬀerentiation according to the economic activities grouping based on the signiﬁcance and eﬃciency of their performance. The most appropriate industrial policy tools for each of the economic activities’ groups are determined. Recommendations for the improvement of the industrial policy of Belarus are proposed.
Keywords: industrial development; industrial policy; economic growth; industrialisation; Belarus